Prevalence and Detection of Pharmaceuticals in Hospital Wastewater: A Case of Referral and District Hospitals in Zanzibar - Mpatani, Farid Mzee; Kombo, Ussi Makame; Ally, Mayassa Salum; Simai, Burhani Othman; Fakih, Mwanaisha Juma; Mbarak, Saide Abdulla; Is-haka, Hassan Vuai; Ame, Ali Makame; Mnemba, Shaib Silima; Haji, Hajra Mohamed; Juma, Bariki Salum; Khamis, Mohammed Hamduni; et al. (Fine Chemical Engineering, 2023)
Despite the great efforts taken by the developed and some developing countries in managing the release of pharmaceuticals from their primary sources to the environment; the pharmaceutical wastewater management in Zanzibar-Tanzania still has not received much attention as a bulk of pharmaceuticals and their metabolites are released to the environment without proper treatment. Therefore, this study has scrutinized the incidence of pharmaceuticals in wastewater released from the referral and district hospitals in Zanzibar, to ascertain the levels of pharmaceuticals present in hospital wastewater. Purposive sampling was implemented to collect a total of seventy-two (72) wastewater samples in a period of six months (March-August 2022). Samples were collected in the effluent of wastewater-streams (Mnazi Mmoja Hospital, MMH) and pit latrines (Kivunge District Hospital (KDH) and Makunduchi District Hospitals (MDH)). The pharmaceuticals in these samples were obtained via the solid phase extraction after which they were analyzed using the LC-tandem MS (Agilent 1,290 LC coupled to 6,460-triple quadrupole MS). The limit of detections (LODs) and limit of quantitations (LOQs) for the determination of pharmaceuticals were in the range of 0.021-0.037 μg L-1 and 0.033-0.059 μg L-1, respectively. The detected analytes belonged to antibiotics, anti-inflammatory, benzodiazepine, antipsychotic, antipyretic and anticonvulsant (anti-epileptic) drugs. Diclofenac (DIC), paracetamol (PCT), ciprofloxacin (CIP), sulfamethoxazole (SMZ) and azithromycin (AZM) were detected at higher concentrations (> 0.25 μg L-1) in wastewater samples collected from KDH and MDH. Lower concentrations of pharmaceuticals (< 0.10 µg L-1) were identified in MMH wastewater samples. These present findings provide estimable information on the incidence of pharmaceuticals in wastewater that can assist in strengthening the environmental strategies for the protection of marine and terrestrial life from pharmaceutical pollution in Zanzibar.